Physiological regulation of marathon performance - Coyle, E. F. (Sports Medicine, 2007)
Running a marathon at the fastest speed possible appears to be regulated by the rate of aerobic metabolism (i.e. marathon oxygen uptake) of a limited amount of carbohydrate energy (i.e. muscle glycogen and blood glucose) and the velocity that can be maintained without developing hyperthermia. According to a model proposed by Joyner in 1991, people possess the physiological ability to run a marathon in [almost equal to]1:58:00. This could be accomplished if the current world record pace for the 'half-marathon' is maintained for the entire marathon. The ultimate limit to marathon performance might be dictated by the limits of running economy and a recruitment of the running musculature with a pattern that minimises fatigue, possibly by spreading the work over many motor neuron.